Irenaeus of Lyons: identifying Christianity - Behr, John (Christian theology in context, 2013)
In this contextual study of Irenaeus of Lyons, the first great theologian of the Christian tradition, John Behr sets Irenaeus both within his own context of the second century and our contemporary context